Animal migration amid shifting patterns of phenology and predation: lessons from a Yellowstone elk herd. Issue 6 (1st June 2013) - Middleton, Arthur D.; Kauffman, Matthew J.; McWhirter, Douglas E.; Cook, John G.; Cook, Rachel C.; Nelson, Abigail A.; Jimenez, Michael D.; Klaver, Robert W.
Abstract : Migration is a striking behavioral strategy by which many animals enhance resource acquisition while reducing predation risk. Historically, the demographic benefits of such movements made migration common, but in many taxa the phenomenon is considered globally threatened. Here we describe a long‐term decline in the productivity of elk ( Cervus elaphus ) that migrate through intact wilderness areas to protected summer ranges inside Yellowstone National Park, USA. We attribute this decline to a long‐term reduction in the demographic benefits that ungulates typically gain from migration. Among migratory elk, we observed a 21‐year, 70% reduction in recruitment and a 4‐year, 19% depression in their pregnancy rate largely caused by infrequent reproduction of females that were young or lactating. In contrast, among resident elk, we have recently observed increasing recruitment and a high rate of pregnancy. Landscape‐level changes in habitat quality and predation appear to be responsible for the declining productivity of Yellowstone migrants. From 1989 to 2009, migratory elk experienced an increasing rate and shorter duration of green‐up coincident with warmer spring–summer temperatures and reduced spring precipitation, also consistent with observations of an unusually severe drought in the region. Migrants are also now exposed to four times as many grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) as resident elk. Both of these restored predators consume migratory elk calves at high rates in the Yellowstone wilderness but are maintained at low densities via lethal management and human disturbance in the year‐round habitats of resident elk. Our findings suggest that large‐carnivore recovery and drought, operating simultaneously along an elevation gradient, have disproportionately influenced the demography of migratory elk. Many migratory animals travel large geographic distances between their seasonal ranges. Changes in land use and climate that disparately influence such seasonal ranges may alter the ecological basis of migratory behavior, representing an important challenge for, and a powerful lens into, the ecology and conservation of migratory taxa.